Effect of the combination of curcuminoid and essential oil on the serum ureum and creatinine level of patientswith osteoarthritis - Kertia, Nyoman; ., Danang (Indonesian Journal of Pharmacy, 2011)
The curcuminoid of Curcuma domesticaVal. rhizome and the essential oil of Curcuma xanthorrhizaRoxb. rhizome can be used for rheumatic treatment,but no enough  data  regarding  those  side  effects.   This  study  aimed  to  determine  the efect  of  curcuminoid  of  Curcuma  domestica Val.  combined  with  essential  oil  from Curcuma  xanthorriza Roxb.  to  the  serum  ureum  and  creatinine  level  of  patients with osteoarthritis. This treatment was compared tothat of piroxicam. This was a Prospective  Randomized  Open  end  Blinded  Evaluation  (PROBE),  involving  38 patients with knee osteoarthritis.The treatment group were given the combination of  15  mg  curcuminoid  of  Curcuma  domestica Val.  and  100  mg  essential  oil  of Curcuma xanthorrhizatwice daily for two weeks. The control group were given 10 mg piroxicam twice daily for two weeks. In the treatment group the serum ureum level  decreased  4.58±6.20%  mg,  while  in  the  control group  the  ureum  level increased  1.68±8.24%  mg.  In  the  treatment  group  the serum  creatinine  level decreased  0.12±0.36%  mg,  while  in  the  control  group the  creatinine  level increased  0.18±0.29%  mg.  Decreasing  of  serum  ureum  level  in  the  treatment group was significantly different compared to increasing of that level in the control group  (p<0.01).  Decreasing  of  the  creatinine  level  in  the  teatment  group  was significantly  different  compared  to  increasing  of  that  level  in  the  control  group (p<0.01).Key words: Curcuminoid, Essential Oil, Ureum, Creatinine, Osteoarthritis